Trouble Songs: A Musicological Poetics - Johnson, Jeff T. (punctum books, 2018)
Trouble Songs is a hybrid serial work that tracks the appearance of the word "trouble" in 20th- and 21st-century American music. It reads (and sings) songs and poems, with reference to cultural events ranging from the death of a pop singer to the growth of popular resistance movements. The trouble singer invokes the word "trouble" in place of actual trouble-the song is a spell that conjures trouble (from bad luck and disaffection to infidelity, impotence, destitution, and the specter of death) in a temporary form that can be dis-spelled, if only for the length of the song. Singer and song also open a critical space for making trouble, for stirring the heart and mind. This space is a disjunction in time (and a superimposition of events) where singer and listener collaborate on meaning (un/)making as they temporarily transform trouble.